Evaluation Procedures as Catalyst For Implementation of Islamic Studies Curriculum in Schools of Arabic and Islamic Studies in North-West Nigeria - Danzaria, Nasir; Frances, Torpev T; Ibrahim, Tanimu Adam (International Research-Based Education Journal, 2024)
This study was on compliance with evaluation procedures as catalyst for implementation of Islamic studies curriculum in schools of Arabic and Islamic studies in North-West Nigeria. It was guided by one research objective, one research question and one null hypothesis. The study adopted descriptive research design with population that comprised 1,394 Islamic studies teachers and 10,037 students. 306 Islamic studies teachers and 378 students were selected as samples of the study based on the Research Advisors (2006) table for determining sample size. Purposive sampling technique was used in selecting the sample States for the study which comprised Katsina, Kano, Kaduna and Jigawa States. The States were clustered according to zonal education offices, schools and respondents, where simple random sampling technique was used in selecting the schools and respondents from the clustered zones. The instruments used for the study was Teachers’ Questionnaire for Evaluation of Islamic Studies Curriculum Implementation (TQEISCI). The data collected was analyzed using descriptive statistics in answering the research question and t-test for independent samples in testing the null hypothesis at 0.05 level of significance. The findings revealed that there is no significant difference in the teachers’ assessment on the level of compliance with evaluation procedures leading to certification in the schools of Arabic and Islamic studies in North-West, Nigeria based on school location. That is to say, there is high level of compliance with evaluation procedures leading to certification of the Schools of Arabic and Islamic studies based on the school location in North-West Nigeria by the Islamic studies teachers. It was recommended that Teachers should be encouraged to maintained compliance with evaluation procedures in the process of teaching and learning Islamic studies.